2015
DOI: 10.1371/journal.pone.0126719
|View full text |Cite
|
Sign up to set email alerts
|

Orexinergic Neurotransmission in Temperature Responses to Methamphetamine and Stress: Mathematical Modeling as a Data Assimilation Approach

Abstract: Experimental DataOrexinergic neurotransmission is involved in mediating temperature responses to methamphetamine (Meth). In experiments in rats, SB-334867 (SB), an antagonist of orexin receptors (OX1R), at a dose of 10 mg/kg decreases late temperature responses (t>60 min) to an intermediate dose of Meth (5 mg/kg). A higher dose of SB (30 mg/kg) attenuates temperature responses to low dose (1 mg/kg) of Meth and to stress. In contrast, it significantly exaggerates early responses (t<60 min) to intermediate and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Therefore, the aforementioned intricate dose dependence is a result of delicate balance between activation of excitatory and inhibitory pathways controlling heat generation (Molkov and Zaretsky ), while both components are mediated by orexinergic neurotransmission (Behrouzvaziri et al. ). In that study, based on existing literature data, we explicitly assumed that at room temperature amphetamines do not increase heat dissipation; an assumption that may require reassessment in light of the findings presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the aforementioned intricate dose dependence is a result of delicate balance between activation of excitatory and inhibitory pathways controlling heat generation (Molkov and Zaretsky ), while both components are mediated by orexinergic neurotransmission (Behrouzvaziri et al. ). In that study, based on existing literature data, we explicitly assumed that at room temperature amphetamines do not increase heat dissipation; an assumption that may require reassessment in light of the findings presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory drive (Inh) puta- tively originates from supramedullary (preoptic nucleus or ventrolateral periaqueductal gray matter) and/or intramedullary (rostroventral lateral medulla) structures. Previously, we demonstrated that temperature responses to Meth are mediated by orexinergic neurotransmission (1). Moreover, using our mathematical model (11), we inferred that both the excitatory and inhibitory components are likely to be activated by orexinergic signals induced by Meth administration.…”
Section: Putative Neuronal Structures and Neurotransmissionmentioning
confidence: 60%
“…First, amphetamines induce arousal, which could be due to alterations in the neuronal activity controlling circadian rhythms. Administration of Meth results in the activation of orexin-containing neurons (1)(2)(3), which are critical for normal circadian rhythmicity and are activated during the active phase of the day cycle. Chronic use of Meth leads to disruption of normal circadian rhythmicity.…”
Section: Introductionmentioning
confidence: 99%
“…As shown above, at equilibrium, if there is no heat exchange between the organ and its environment (other than through the circulation), the organ temperature cannot be more than 1.3 C higher than the arterial blood temperature. Furthermore, the core temperature in rats fluctuates between »37 and 38 C, with a potential to decrease to »36 C during sleep [25,26] and to increase to »39 C during intense exercise [27][28][29][30][31][32] or pharmacological stimulation [33][34][35]. As such, the physiological range of the core temperature is almost three times wider than the maximum effect of local metabolism.…”
Section: Brain Temperaturementioning
confidence: 99%
“…Obviously, in extreme situations, deep core body temperature may be even lower than 36 C or higher than 39 C, but the brainblood temperature gradient is still bounded by 1.3 C. This does not diminish the importance of local metabolism; in many situations, having a brain temperature 1.3 C lower or higher is equivalent to living or dying (see, e.g., ref. [35]).…”
Section: Brain Temperaturementioning
confidence: 99%